City body - Colleti, Julia (Re-visiones, 2025)
City Body, Angelika Loderer’s solo exhibition at SOPHIE TAPPEINER, explores the hidden infrastructures of urban life—waste, maintenance, and communication—through sculptural works that transform discarded materials into sites of metamorphosis. Engaging with theories of urban metabolism and care, Loderer reveals how matter persists beyond consumption, exposing the fractures in capitalist systems that fail to reabsorb their own waste. From corroded debris to fungal networks overtaking obsolete objects, her works suggest alternative cycles of repair and transformation. City Body invites viewers to reconsider the city as a living, digesting entity—where nothing truly disappears, but continually reshapes what remains.